Pemanfaatan Endorsement TikTok Sebagai Media Pemasaran Digital Produk Somenthic: (Studi kasus Pada Mahasiswa FIS Ilmu Komunikasi UINSU Stambuk 2021) - Zahra Ramadhan; Kasron (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to describe the use of endorsements on the TikTok platform as a digital marketing medium for Somethinc beauty products. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, observations, and documentation of endorsement content carried out by TikTok influencers. The results of the study indicate that the endorsement strategy on TikTok is able to increase brand awareness and encourage consumer purchasing decisions, especially among teenagers and young adults. The determining factors for the success of this strategy include influencer credibility, creative content delivery style, and the suitability between the influencer's persona and Somethinc's brand image. Thus, TikTok endorsements have proven to be an effective digital marketing tool in reaching a wide audience and building emotional relationships between brands and consumers.